Speech-Language Pathologists' Practices and Attitudes Toward App Use in Therapy - (:unkn) unknown (My University, 2018)
Numerous national surveys have established that Americans of all ages are using mobile technologies (e.g. cell phones, smartphones, and tablets) more than ever before (Pew Research Center, 2018; American Academy of Pediatrics, 2016a; American Academy of Pediatrics, 2016b; Reid-Chassiakos et al., 2016; Tsetsi & Rains, 2016; Kabali et al., 2015). In the same vein, Morris, Jones, and Sweatman (2016) found that Americans with visual, hearing, motor, learning, and speech disabilities area also engaging with apps on smartphone and tablet technologies for vocational, educational, and social purposes. Developers of the iOS and Android operating systems have prioritized user-friendly design and accessibility features to improve access of mobile technologies to the greatest number of users (“Android Accessibility Help,” 2017; Apple, 2017). Rehabilitation professionals are interested in changing or modifying behaviors to help their clients meet therapy goals and access high quality of life outcomes. Multiple resources have supported that people form new behaviors and habits related to use of their smartphones (Peters, 2009; Wood & Neal, 2008; Oulasvirta, Rattenbury, Ma, & Raita, 2012); therefore, smartphone apps could possibly assist rehabilitation professionals when providing treatment to people with disabilities. Other survey-based studies of Occupational Therapists (OTs) (Kyaio, 2015) and Speech-Language Pathologists (SLPs) (Zajc, Istenic-Starcic, Lebenicnik, & Gacnik, 2018) have confirmed that app-based interventions and therapy tools have already infiltrated the field of rehabilitation (Peters, 2009; Wood & Neal, 2008; Oulasvirta et al., 2012), despite the lack of evidence establishing the efficacy of many app-based interventions (Newmann, 2017; Papadakis, Kalogiannakis, & Zaranis, 2017b; Schoen-Simmons, Paul, & Shic, 2016; Erickson, 2015; Stone-MacDonald, 2014). Collectively, these studies highlight the urgency of integrating evidence-based practice (EBP) into an SLP’s service delivery decisions related to app use, especially now that apps and mobile technologies are being developed and available for purchase by the public at unprecedented rates. The purpose of this study was to survey practicing, certified SLPs in the U.S.A. to examine current attitudes and opinions toward the use of apps for purposes related to speech-language therapy. This survey was conducted utilizing the Qualtrics survey platform to maximize data security, access data, and perform data analysis. The web-based survey consisted of 48 questions which were designed to (1) examine common trends in demographic features of SLPs who use apps in therapy, (2) examine the purposes for which apps were used and which skills SLPs targeted when using apps in therapy, (3) examine the variety of barriers which SLPs may face when using apps or mobile technologies in therapy, and (4) examine the factors which SLPs consider when purchasing apps. There were 228 SLPs who participated in the study. All had their certificate of clinical competence (CCC-SLP) or were currently in their clinical fellowship year (CFY-SLP) and practiced in the United States of America. Results of the study indicate that therapists of varying demographic features who see patients across pediatric and adult settings are using apps to target therapy goals. Clinical implications and directions for future research are discussed.
Keywords: apps; communication disorders; mobile technology; speech-language pathologist; speech-language pathology; speech therapy